Lacunary d-Statistical Boundedness of Order ? in Metric Spaces - Kandemir, H. Sengul; Et, M.; Cakalli, H. (Inst Math & Mechanics Azerbaijan, 2022)
In this study, using a lacunary sequence we introduce the concepts of lacunary d-statistically convergent sequences of order alpha and lacunary d-statistically bounded sequences of order alpha in general metric spaces.
Keywords: statistical convergence; lacunary sequence; metric space